Differentiated Instruction in Secondary Mathematics - Amadio, Rachel (My University, 2014)
Response to Intervention (RtI) is a framework used to increase student performance by continuously monitoring student progress and then differentiating instruction to meet students' needs (Minnesota Department of Education, 2013b). The Minnesota Department of Education recommends that schools implement RtI as one method to improve student academic success. While differentiated instruction is endorsed by the Minnesota Department of Education, it is unknown how effective differentiated instruction is in secondary mathematics as perceived by teachers at the secondary level in a metropolitan school district in Minnesota. This study examined teachers' perceptions about the effectiveness or lack of effectiveness of differentiated instruction in secondary mathematics in a metropolitan school district in Minnesota. This study used a survey and teacher interviews to build understanding of teachers' perceptions. The researcher concluded, based on the results, that secondary mathematics teachers in the metropolitan school district in Minnesota would benefit from more time, more concise curriculum, and more professional development to effectively implement differentiated instruction in secondary mathematics.
Keywords: secondary mathematics; RTI; Response to Intervention; Educational Leadership; Minnesota Department of Education